Values and attributes of volleyball by the fans in the FIVB Men's World Championships 2014 - Koljonen, Saana (2015)
As the world of sport is encountering challenges, such as intensified competition, fragmented markets and loss of commitment, there is a need to discover new insights of the global sport consumers to gain more understanding of their behavior. Volleyball world is not an exception as regards the challenges. Despite its popularity, however, volleyball has not been researched as widely as for example football.